2008
DOI: 10.1002/jca.20180
|View full text |Cite
|
Sign up to set email alerts
|

Plasmapheresis and intravenous immune globulin for the treatment of D alloimmunization in pregnancy

Abstract: The alloimmunized pregnancy can result in fetal and newborn mortality due to fetal anemia. Control of fetal anemia has not been possible until recently, and management consists of following the degree of fetal anemia during gestation until intrauterine transfusion is feasible to support the fetus until delivery. Cordocentesis and intrauterine transfusion have potential complications that have been well documented. Control of fetal anemia via immune modulation utilizing plasmapheresis and intravenous immune glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…Maternal antibody titers were reduced, IUT seemed to be postponed and all babies were alive and well at birth [78]. Several case reports have been published with favorable outcome following this combined approach [86,[92][93][94][95][96]. Reported side effects of IVIG are rare but may include: headache, fever, myalgia and low back pain, rush or chills, urticaria, nausea and vomiting, tachycardia, chest tightness, hypotension and shortness of breath [42,50,97,98].…”
Section: Intravenous Immunoglobulins (Ivig)mentioning
confidence: 99%
“…Maternal antibody titers were reduced, IUT seemed to be postponed and all babies were alive and well at birth [78]. Several case reports have been published with favorable outcome following this combined approach [86,[92][93][94][95][96]. Reported side effects of IVIG are rare but may include: headache, fever, myalgia and low back pain, rush or chills, urticaria, nausea and vomiting, tachycardia, chest tightness, hypotension and shortness of breath [42,50,97,98].…”
Section: Intravenous Immunoglobulins (Ivig)mentioning
confidence: 99%
“…These fi ndings are consistent with other reports, which confi rm that early plasmapheresis followed by the use of high-dose maternal IVIG could be benefi cial in early treatment of severe Rh-alloimmunized pregnancies [16,34] . There are also three articles reporting a total of eight patients with poor obstetrical history who were treated with both plasmapheresis and IVIG administration according to their antibody titers, and all had live-born infants without undergoing transfusion therapy [23,54,91] . A potential explanation for the enhanced perinatal survival reported in these series is that plasma exchange can remove the damaging antibodies but cannot inhibit further antigen stimulation; the adjuvant administration of IVIG would retain this decline in antibody levels, inhibiting a " rebound " effect soon after treatment in the majority of patients [66] .…”
Section: Plasmapheresismentioning
confidence: 99%
“…Several case series and case reports indicate a beneficial role of IVIG, at least in delaying the development of significant anemia [36]. Admittedly, focusing on the reported cases in the literature, the administration of IVIG varied considerably and was inadequate due to low doses, delayed administration (after fetal anemia was already present), and/or inconsequent administration in a number of cases (table 2) [30,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. Only one study has shown that the administration of 1 g/kg/week in four women with anti-D did not appear to improve outcomes of affected fetuses [58].…”
Section: Discussionmentioning
confidence: 99%